Effects of dielectric flow rate in electrical discharge machining of aerospace materials - Law, Kai Rong (2019)
Internal flushing in Electrical Discharge Machining (EDM) is of paramount importance to achieving good machining efficiency and high-quality results. The machinability of two aerospace grade materials – Titanium Ti-6Al-4V Alloy and Inconel 625 Nickel-based Alloy by micro-EDM process will be investigated by applying different machine parameters to the Agie Charmilles Form 20. Both Ti-6Al-4V and Inconel 625 alloy are widely used among advanced aerospace application due to their remarkable strength to weight ratio, resistance to corrosion and excellent thermal properties. This project aims to analyze the effects of dielectric flow rates at different flushing pressures – 0.2 MPa, 2.0 MPa, 4.0 MPa and 8.0 MPa on various output parameters. In addition, the introduction of rotary tool electrodes at varying speeds – 100 rpm, 1000 rpm and 2000 rpm will provide additional insights on correlation between rotating tool electrodes and different flow rates. The parameters of the machining efficacy to be evaluated in this project include the Material Removal Rate (MRR) and Tool Wear Rate (TWR). The qualities of the features by micro-EDM – geometrical accuracy and surface finishes will be taken into account to ascertain the capability of micro-EDM processes. The experimental results revealed that increasing flushing pressure generally improves MRR but beyond a certain pressure, MRR eventually decreases. It is noted that MRR is the highest at 1000 rpm but further increase in electrode rotation speeds only leads to a minimal decrease by 6% in MRR. Furthermore, increasing flushing pressure leads to lower electrode tool wear but at the same time, it results in poorer workpiece surface geometries.